2014
DOI: 10.1371/journal.pgen.1004320
|View full text |Cite
|
Sign up to set email alerts
|

Null Mutation in PGAP1 Impairing Gpi-Anchor Maturation in Patients with Intellectual Disability and Encephalopathy

Abstract: Many eukaryotic cell-surface proteins are anchored to the membrane via glycosylphosphatidylinositol (GPI). There are at least 26 genes involved in biosynthesis and remodeling of GPI anchors. Hypomorphic coding mutations in seven of these genes have been reported to cause decreased expression of GPI anchored proteins (GPI-APs) on the cell surface and to cause autosomal-recessive forms of intellectual disability (ARID). We performed homozygosity mapping and exome sequencing in a family with encephalopathy and no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
81
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 74 publications
(88 citation statements)
references
References 39 publications
6
81
0
Order By: Relevance
“…The LCLs of the affected individual were resistant to PI-PLC, indicating that the GPI-APs are structurally abnormal, whereas the parents showed a partial resistance. These results are in line with the reported family with PGAP1 variants by Murakami et al 15 The other family reported by Novarino et al 29 was not tested. Besides a developmental delay, the phenotype is variable.…”
Section: Pi-plc Treatment and Facs Analysissupporting
confidence: 89%
See 4 more Smart Citations
“…The LCLs of the affected individual were resistant to PI-PLC, indicating that the GPI-APs are structurally abnormal, whereas the parents showed a partial resistance. These results are in line with the reported family with PGAP1 variants by Murakami et al 15 The other family reported by Novarino et al 29 was not tested. Besides a developmental delay, the phenotype is variable.…”
Section: Pi-plc Treatment and Facs Analysissupporting
confidence: 89%
“…[22][23][24]40,41 ALP was not measured in the PGAP1-affected individuals, but in PGAP1-deficient cells, no diminished cell-surface expression of GPI-APs was measured, making elevated ALP levels less likely. 15 In addition, the typical facial dysmorphisms of Mabry syndrome, consisting of apparent hypertelorism, long palpebral fissures, short nose with broad nasal bridge and tip and tented upper lip vermillion, were not present in the here presented individual.…”
Section: Pi-plc Treatment and Facs Analysismentioning
confidence: 62%
See 3 more Smart Citations